PARTISIPASI MASYARAKAT DALAM KEGIATAN WISATA BATIK DI DESA WUKIRSARI, KABUPATEN BANTUL - Meilania, Meilania; Rahmi, Dwita Hadi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2019)
Community-based tourism is closely related to the active involvement of local communities in the development of tourism in their environment. Community participation in maintaining and developing batik tourism activities is the main attraction in the Wukirsari village. The development of Wukirsari village into a leading tourist destination in Bantul Regency can be an example for other tourist villages. This is interesting to study by describing and identifying the extent to which community participation affects the community to participate in batik tourism activities. The research method used in this study is a descriptive research method with a qualitative approach that is carried out by in-depth interviews with the parties concerned and direct observation in the field to obtain a direct picture based on empirical conditions. The field results are then analyzed by reducing data and triangulation so that the data obtained is valid so that it can draw a conclusion. The results of the discussion on community participation in tourism activities are, in general, local communities involved in the planning, implementation, evaluation, and distribution of benefits. But it is still necessary to maximize the participation of people who have not been directly involved in tourism activities. The most dominant form of local community participation is in the form of energy.